Anticoagulants after Discharge in Patients with COVID-19: What we Know at the End of 2021 - I. S. Yavelov (Столичная издательская компания, 2022)
This review discusses reasons for prolonged use of anticoagulants after discharge of patients with COVID-19 without additional indication for anticoagulation. Data regarding rate of thrombotic and thromboembolic complications in patients with COVID-19 after discharge from the hospital are presented. Large randomized controlled trials EXCLAIM, ADOPT, MAGELLAN, APEX  and MARINER with prolonged use of anticoagulants in patients hospitalized  with acute nonsurgical diseases  before pandemia  of COVID-19 are discussed.  The first prospective  randomized controlled  trial MICHELLE with direct oral anticoagulant rivaroxaban in a dose 10 mg once daily after discharge of patients with COVID-19 with high risk at least venous thromboembolism are analyzed. It seems that the most relevant approach  for the determination  of indications for prolonged use of anticoagulants in doses dedicated for primary prevention of venous thromboembolism after discharge of patients with COVID-19 without apparent indication for anticoagulation is a modified IMPROVE VTE risk score with the addition of elevated in-hospital D-dimer  level. And the most well-studied approach  for anticoagulation in these patients is a direct peroral anticoagulant rivaroxaban 10 mg once daily for 35 (and  possibly up to 45) days after discharge.